Metastatic Renal Cell Carcinoma Presenting as a Paranasal Sinus Mass: The Importance of Differential Diagnosis - Massimo Ralli; Giancarlo Altissimi; Rosaria Turchetta; Mario Rigante (Case Reports in Otolaryngology)
Metastases in the paranasal sinuses are rare; renal cell carcinoma is the most common cancer that metastasizes to this region. We present the case of a patient with a 4-month history of a rapidly growing mass of the nasal pyramid following a nasal trauma, associated with spontaneous epistaxis and multiple episodes of hematuria. Cranial CT scan and MRI showed an ethmoid mass extending to the choanal region, the right orbit, and the right frontal sinus with an initial intracranial extension. Patient underwent surgery with a trans-sinusal frontal approach using a bicoronal incision combined with an anterior midfacial degloving; histological exam was compatible with a metastasis of clear cell renal cell carcinoma. Following histological findings, a total body CT scan showed a solitary 6 cm mass in the upper posterior pole of the left kidney identified as the primary tumor. Although rare, metastatic renal cell carcinoma should always be suspected in patients with nasal or paranasal masses, especially if associated with symptoms suggestive of a systemic involvement such as hematuria. A correct early-stage diagnosis of metastatic RCC can considerably improve survival rate in these patients; preoperative differential diagnosis with contrast-enhanced imaging is fundamental for the correct treatment and follow-up strategy.